2021
DOI: 10.24042/ajpm.v12i2.9645
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Indonesian primary school students’ mathematical critical thinking skills through problem-based learning: A meta-analysis

Abstract: The synthesis of some empirical researches revealed that the implementation of problem-based learning (PBL) has a heterogeneous effect size on the mathematical critical thinking skills (MCTS) of primary school students in Indonesia. However, it seems that no researches were investigating the causative factors of the heterogeneity of primary students’ MCTS through PBL. Therefore, this meta-analysis research was employed to examine three potential factors that were PBL class capacity, PBL treatment duration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Table 3 shows that the studies number that had to be removed or added to this study was 0. It indicates that the distribution of effect size data in the funnel plot was symmetrical (Nugraha & Suparman, 2021;Nurjanah et al, 2020). Moreover, six documents reported that the use of Cabri 3D had a strong positive effect on the students' mathematical academic outcome (Adirakasiwi & Warmi, 2018;Hendriana et al, 2019;Kariadinata et al, 2019;Marlena & Nugrheni, 2019;Saumi & Amalia, 2018;Widiastuti & Kurniasih, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Table 3 shows that the studies number that had to be removed or added to this study was 0. It indicates that the distribution of effect size data in the funnel plot was symmetrical (Nugraha & Suparman, 2021;Nurjanah et al, 2020). Moreover, six documents reported that the use of Cabri 3D had a strong positive effect on the students' mathematical academic outcome (Adirakasiwi & Warmi, 2018;Hendriana et al, 2019;Kariadinata et al, 2019;Marlena & Nugrheni, 2019;Saumi & Amalia, 2018;Widiastuti & Kurniasih, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Critical Thinking (CT) Ability is one of the focuses of 21st-century learning (Basri et al, 2019;Changwong et al, 2018;Marzuki, 2021;Nugraha & Suparman, 2021). CT skills are very important for students because it has the potential to help them to solve problems when in difficult situations.…”
Section: Introductionmentioning
confidence: 99%